Assessing how adult attachment and gender role attitudes impact intimate partner violence - Bratanch, Theresa M. (2017)
Intimate partner violence (IPV) describes the physical, sexual or psychological violence and abuse by a former partner or spouse. This study explored the relationship between adult attachment style and gender role attitudes, and level of physical violence and coercive control present in an intimate relationship. This dataset is drawn from a larger research study of male batterers who participated in the domestic violence program of the Circuit Court of Cook County Social Services Department (DVP). This data was collected from November 2001 through April 2003 and includes quantitative data for one hundred fifty-four men. Attachment Style was measured using the “Relationship Scales Questionnaire” (RSQ), an instrument used to assess attachment style in close relationships. Gender Role Attitude was measured using the Sex Role Egalitarianism Scale (SRES), an instrument that accounts for a person’s attitude towards the equality of men and women. Level of physical violence was measured using the “Revised Conflict Tactics Scale” (CTS2), and the “Psychological Maltreatment of Women Index” (PMWI) was used to measure the amount of control participants exerted in their intimate relationship. Overall fearful-avoidant attachment produced a statistically significant relationship with both level of physical abuse and emotional-verbal coercive control, and anxious-avoidant attachment produced a statistically significant relationship with emotional-verbal coercive control. Conclusions, limitations of the study, and future directions for research are discussed